Factors influencing the foreign consumer towards intention to continuously use of food delivery service in Malaysia - Chun, Zi Chien (2019)
This research focuses on the attempt to investigate factors that influence the foreign consumer towards food delivery apps in Malaysia. The purpose of conducting this research is to examine the relationship between convenience, design, trustworthiness, price, various food choice, service quality and perceived value towards intention to continuously use food delivery services in Malaysia. The data for this study was collected using survey questionnaire. For this research, the targeted population is foreign consumer who stay in Klang Valley and used food delivery apps in Malaysia before. A sample size of 185 sets of questionnaires was distributed to foreign consumer in UCSI university and Kuala Lumpur Sentral (KL Sentral). Moreover, the Statistical Package for Social Sciences (SPSS) version 21 is being used to analyse the data collected throughout the survey. In addition, regression analysis revealed that “Convenience”, “Trustworthiness” and “Various Food Choice” was the most significant predictor towards Perceived value, and followed by “Service Quality”, “Price” and “Design” . The findings suggested that the design interface of food delivery apps must be user friendly. Besides, food delivery industry also recommended to hire more riders and using better pouch to maintain the food quality. Practical contributions are discussed, with future research suggested.